Towards Doping Optimization of Semiconductor Lasers. Issue 5 (28th July 2016) - Peschka, D.; Rotundo, N.; Thomas, M.
ABSTRACT: We discuss analytical and numerical methods for the optimization of optoelectronic devices by performing optimal control of the PDE governing the carrier transport with respect to the doping profile. First, we provide a cost functional that is a sum of a regularization and a contribution, which is motivated by the modal net gain that appears in optoelectronic models of bulk or quantum-well lasers. Then, we state a numerical discretization, for which we study optimized solutions for different regularizations and for vanishing weights.